Design and Synthesis of Fluorescent Acyclic Nucleoside Phosphonates as Potent Inhibitors of Bacterial Adenylate Cyclases. (24th October 2016) - Břehová, Petra; Šmídková, Markéta; Skácel, Jan; Dračínský, Martin; Mertlíková‐Kaiserová, Helena; Velasquez, Monica P. Soto; Watts, Val J.; Janeba, Zlatko
Abstract: Bordetella pertussis adenylate cyclase toxin (ACT) and Bacillus anthracis edema factor (EF) are key virulence factors with adenylate cyclase (AC) activity that substantially contribute to the pathogenesis of whooping cough and anthrax, respectively. There is an urgent need to develop potent and selective inhibitors of bacterial ACs with prospects for the development of potential antibacterial therapeutics and to study their molecular interactions with the target enzymes. Novel fluorescent 5‐chloroanthraniloyl‐substituted acyclic nucleoside phosphonates (Cl‐ANT‐ANPs) were designed and synthesized in the form of their diphosphates (Cl‐ANT‐ANPpp) as competitive ACT and EF inhibitors with sub‐micromolar potency (IC50 values: 11–622 nm ). Fluorescence experiments indicated that Cl‐ANT‐ANPpp analogues bind to the ACT active site, and docking studies suggested that the Cl‐ANT group interacts with Phe306 and Leu60. Interestingly, the increase in direct fluorescence with Cl‐ANT‐ANPpp having an ester linker was strictly calmodulin (CaM)‐dependent, whereas Cl‐ANT‐ANPpp analogues with an amide linker, upon binding to ACT, increased the fluorescence even in the absence of CaM. Such a dependence of binding on structural modification could be exploited in the future design of potent inhibitors of bacterial ACs. Furthermore, one Cl‐ANT‐ANP in the form of a bisamidate prodrug was able to inhibit B. pertussis ACT activity in macrophage cells with IC50 =12 μm . Abstract : The time to ACT is now ! Bacterial adenylate cyclases as potential drug targets: This study focused on novel fluorescent acyclic nucleoside phosphonates as potent inhibitors of adenylate cyclase toxin (ACT) from Bordetella pertussis and edema factor (EF) from Bacillus anthracis . The prepared fluorescent compounds are excellent tools to study the molecular interactions between bacterial adenylate cyclases and their potential inhibitors.